Prestasi Belajar Anak Pegawai dan Non Pegawai pada Sekolah Dasar Negeri 26 Baolan Tolitoli - Ansyari (PT FORMOSA CENDEKIA GLOBAL, 2022)
In every educational process, students are input components that have a central position, an educational process cannot take place without the presence of students, called students. When entering a teaching and learning process in schools, students have certain backgrounds that determine their success in following the learning process and naturally students have different characteristics. The main problem in this study is whether there is a difference in the learning achievement of children of employees and non-employees and whether the work (profession) of parents can affect the learning process. The theory that strengthens this research uses several theories related to the title, namely the notion of learning, the notion of motivation, the notion of learning achievement, the factors that influence learning. To provide answers to questions and to prove the hypothesis, qualitative analysis methods are used. Based on the results of the discussion of this study, it can be stated that the work of parents has no effect on children's learning achievement.